Investigations on the mechanical behavior of composite pipes considering process-induced residual stress - Yang, Xufeng (2023)
Hydrogen, as a clean energy source, has gained worldwide attention due to its high energy density and diverse manufacturing methods. Pipeline transportation is the most important way for long-distance transportation of hydrogen. However, hydrogen embrittlement due to hydride formation in metals will induce cracking in the pipeline structures. Composites pipes are good alternatives to metals as their excellent compatibility with hydrogen. This paper aims to carry out the preliminary design of composite hydrogen transportation pipelines. Firstly, the Thermo-Consolidation/Curing-mechanical analysis models for the thermosetting composites (T700/3501-6) and thermoplastic composites (T700/HDPE) were established, respectively. The process-induced residual stress of the composite pipelines was predicted by the models. Subsequently, a criterion of hydrogen leakage for the composite pipelines was proposed, and the load-bearing capacity analysis of the composite pipelines was carried out based on the progressive damage model. The simulation results emphasize that the predicted leakage pressure would be overestimated without considering the process-induced residual stress. The leakage pressures of composite pipelines with and without liner are calculated and compared, the results showed that the thermoplastic composite pipes with liner are the most suitable for hydrogen transportation.